2016
DOI: 10.1007/s10142-016-0502-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression profiling of DNA methyltransferases during development and stress conditions in Solanaceae

Abstract: DNA methyltransferase (DMTase) enzymes contribute to plant development and stress responses by de novo establishment and subsequent maintenance of DNA methylation during replication. However, the molecular mechanism underlying this activity remains obscure, especially in crop species. Using DMTase homolog complement in six Solanaceae species, we demonstrated here that their number remained conserved in Solanum lineage, whereas it was expanded in both pepper and Nicotiana benthamiana. Non-synonymous vs synonymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
3
13
0
Order By: Relevance
“…However, the identification of an analogous number of C5-MTase genes in eggplant, potato and tomato may suggest a similar function within the three phylogenetically closer Solanaceae species. No CMT1-like homologs were revealed in the eggplant genome, as previously observed in other Solanaceae species [48]. This gene, when present, was found to be almost silent in A .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, the identification of an analogous number of C5-MTase genes in eggplant, potato and tomato may suggest a similar function within the three phylogenetically closer Solanaceae species. No CMT1-like homologs were revealed in the eggplant genome, as previously observed in other Solanaceae species [48]. This gene, when present, was found to be almost silent in A .…”
Section: Discussionmentioning
confidence: 58%
“…thaliana and tomato [32] (Table 1). The number of isolated C5-MTases corresponds to that identified in potato, but it is lower than the one reported in pepper (11) and tomato (8) [48]. Eggplant displays one MET1 gene, like tomato and potato, and 3 CMTs, like potato, and only 2 DRMs.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In TGMS line of wheat, the pollen viability is dramatically decreased to complete sterility at a certain low temperature occurring during reproductive development [52,53]. Recent studies have shown that DMT genes contribute to plant stress responses and development by de novo establishment and subsequent maintenance of DNA methylation [71]. However, the transcript abundance of DMT genes in temperature-sensitive genic male sterile wheat has rarely been studied.…”
Section: Structural and Evolutionary Features Of Dmt Genes In Wheatmentioning
confidence: 99%
“…DNA methyltransferases methylate cytosine residues in DNA (Wada ). Plants possess three types of DNA methyltransferases that differ in protein structure and function (Kumar et al ). Maintenance of methylation patterns at CG requires the methyltransferase (MET) class of proteins, whereas plant‐specific chromomethylases (CMTs) are involved in maintenance at CHG and CHH (where H is either C, T or A) (Stroud et al ).…”
Section: Introductionmentioning
confidence: 99%